Performance Analysis of CSI:T Routing in a Delay Tolerant Networks - Hardika Kusuma Putri; Leanna Vidya Yovita; Ridha Muldina Negara (IAES Indonesia Section, 2017)
Delay Tolerant Network (DTN) is a network that allows nodes to move dynamically and doesn’t always provide for end-to-end connection. The dynamically of nodes make the movement of the nodes becomes important. The movement model of nodes will record their behavior and this could be utilized to develop a new routing protocol in DTN. One of the DTN routing protocol that utilize it is CSI: T routing. CSI: T routing viewed a node based on their behavioral profile which is represent the mobility preference. Our study is measure the performance of CSI: T in terms of delivery probability, overhead ratio, and average latency by changing the buffer capacity, packet lifetime, and number of nodes. We used Opportunistic Network Environment (ONE) Simulator for the simulate the real-life scenario of a college-routines.